The Impact of Growth Opportunity, Cash Conversion Cycle on Cash Holding: A Case Study of Textile & Garment Sub-Sector Companies Listed on Indonesia Stock Exchange - Mardhotillah, Dea Ayu; Anwar, Hairul (KINERJA, 2024)
The purpose of this research is to analyse the impact of growth opportunity, cash conversion cycle on cash holding: a case study of textile & garment sub-sector companies listed on Indonesia stock exchange for the period 2016-2020. The data used in this research were secondary data in the form of textile and garment sub-sector companies during 2016-2020 period which consists of 16 companies with an observational data of 80 (balanced data panel). The data were accessed on www.idx.co.id. The method of data analysis with the help of Eviews 10. The result of this research found that the growth opportunity has a positive significant effect on cash holding, and cash conversion cycle has a negative and insignificant effect on cash holding.